Construction of a Multiplex Promoter Reporter Platform to Monitor Staphylococcus aureus Virulence Gene Expression and the Identification of Usnic Acid as a Potent Suppressor of psm Gene Expression - Gao, Peng; Wang, Yanli; Villanueva, Iván; Ho, Pak Leung; Davies, Julian; Kao, Richard Yi Tsun (Frontiers in Microbiology, 2016)
As antibiotic resistance becomes phenomenal, alternative therapeutic strategies for bacterial infections such as anti-virulence treatments have been advocated. We have constructed a total of 20 gfp-luxABCDE dual-reporter plasmids with selected promoters from S. aureus virulence-associated genes. The plasmids were introduced into various S. aureus strains to establish a gfp-lux based multiplex promoter reporter platform for monitoring S. aureus virulence gene expressions in real time to identify factors or compounds that may perturb virulence of S. aureus. The gene expression profiles monitored by luminescence correlated well with qRT-PCR results and extrinsic factors including carbon dioxide and some antibiotics were shown to suppress or induce the expression of virulence factors in this platform. Using this platform, sub-inhibitory ampicillin was shown to be a potent inducer for the expression of many virulence factors in S. aureus. Bacterial adherence and invasion assays using mammalian cells were employed to measure S. aureus virulence induced by ampicillin. The platform was used for screening of natural extracts that perturb the virulence of S. aureus and usnic acid was identified to be a potent repressor for the expression of psm.